Research at the National and European Levels on the Main Fields of Intervention Covered by the EU Directive on Road Infrastructures Safety Management - The Experience of a National Research Laboratory (LNEC) - Macedo, A. L. (2010)
Abstract In November 2008 the European Parliament and the Council of the EU have adopted a Directive aimed at the improvement of road infrastructures safety management within the Trans-European Road Network, that can also be extended as a set of good practices to other national networks, through the implementation by the Member States of procedures relating to: “road safety impact assessments” and “road safety audits” of infrastructure projects; the “safety ranking and management” of the road network in operation; “safety inspections”; and “data management”. In the same Directive it is stated that research activity and the dissemination of its results play an important role in this process. At the Transportation Department of the National Laboratory for Civil Engineering (LNEC), in Portugal, a special attention has been given, over the time, to these and other safety related research topics. In this context, the participation in European projects and collaboration agreements with national road and traffic administrations, have given a support to the studies carried out and a practical ground for the application of their results. Based upon this experience, in this paper a concise description is made on the main aspects of the EU Directive and on their relation with research studies, either already completed or on-going, at the European and national levels, showing how they can provide relevant contributions to the overall objective of a continuous improvement of road traffic safety.